Penanaman Nilai Karakter Sopan Santun Oleh Guru Tahfidz Bagi Siswa Melalui Program Tahfidz Al-Qur’an di SMPN 3 Kinali - Saerofah Saerofah; Salmi Wati; Afrinaldi Afrinaldi; Al Baihaqi Anas (Pusat Riset dan Inovasi Nasional, 2023)
Manners are a form of morals that must be owned by Muslims and is a culture of Indonesian society that needs to be upheld when socializing with other people. This study aims to describe the stages of cultivating polite values ​​through the Tahfidz Al-Qur'an program at SMPN 3 Kinali. This research is a type of field research, namely research with a qualitative approach. Subjects or key informants in this study were Tahfidz teachers and supporting objects or informants were students. To obtain research data, researchers used a set of interview guidelines and observation guidelines as research instruments. Data collection techniques used in this study are observation, interviews and documentation. While the data analysis technique used is using data reduction, data presentation and drawing conclusions. The results of the study show that there are three stages in inculcating the character values ​​of courtesy by the tahfidz teacher for students through the Al-Quran Tahfidz program at SMPN 3 Kinali, namely: First, the moral knowing/learning to know stage (introduction of good values ​​and bad values). At this stage the teacher conveys good and bad values ​​through lectures in the form of presenting cases and delivering advice. Second, the moral loving/moral feeling stage (feelings of love and need for values). At this stage the teacher uses exemplary methods, giving physical touches and conveying inspirational stories from the time of the Prophets and Apostles. Third, the stage of moral doing/learning to do (implementation of good and bad values). This stage is carried out using the habituation method and giving rewards and punishments.